2014
DOI: 10.1007/s13762-014-0659-z
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of humic acid by amine-modified nanocellulose: an experimental and simulation study

Abstract: The purpose of this study was to evaluate the adsorption of humic acid (HA) by amine-modified nanocellulose. At first, nanocellulose was synthesized by acid hydrolysis, and then was modified by N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane. In the next step, HA and amine-modified nanocellulose were incubated at different conditions (pH, incubation time, temperature, and concentration). Furthermore, we used molecular dynamic (MD) simulation for observation of adsorption at molecular scale. For this purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 22 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…The use of nanocellulose (NC) has also been shown to be a promising alternative adsorbent due to its high surface area-to-volume ratio, good mechanical properties and wet strength, low cost, high natural abundance and inherent environmental inertness. 17,18 Moreover, the surface functionalized NC was demonstrated to be capable of removing different kinds of heavy metal ions [21][22][23][24][25] and dyes, [26][27][28][29] as well as different organic pollutants 30,31 by an electrostatic attraction mechanism via introduced acid (carboxylic 21 or phosphate 25 ) or basic (amino 23,27,30 or quarter 26 ) functional groups. Initial studies have also shown that NC can act as a functional adsorbent and/or reinforcing additive when being embedded into a highly hydrophilic biopolymer matrix, providing both anti-or low fouling properties and high adsorption capacity.…”
mentioning
confidence: 99%
“…The use of nanocellulose (NC) has also been shown to be a promising alternative adsorbent due to its high surface area-to-volume ratio, good mechanical properties and wet strength, low cost, high natural abundance and inherent environmental inertness. 17,18 Moreover, the surface functionalized NC was demonstrated to be capable of removing different kinds of heavy metal ions [21][22][23][24][25] and dyes, [26][27][28][29] as well as different organic pollutants 30,31 by an electrostatic attraction mechanism via introduced acid (carboxylic 21 or phosphate 25 ) or basic (amino 23,27,30 or quarter 26 ) functional groups. Initial studies have also shown that NC can act as a functional adsorbent and/or reinforcing additive when being embedded into a highly hydrophilic biopolymer matrix, providing both anti-or low fouling properties and high adsorption capacity.…”
mentioning
confidence: 99%
“…(B)]. In an acidic medium (pH = 5.0), NH 2 groups in CS polymer networks were protonated into – NH3+ groups, which can facilitate to weaken the interaction between CS and PEG polymer chains (cross‐linking density decreased). Consequently, a larger amount of nano RIF was dissolved in the buffer solution and released via diffusion in acidic medium.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, nanocellulose is the subject of a wide spectrum of research efforts in the improvement of rheology modifiers, optical devices, coating components, reinforcing agents, and stabilizers of multiphase systems . In the field of energy application, NCC in different forms has been used; for example, NCC in crystal and fibril forms has been added as an energy adsorbent to increase the reinforcement effect of polymeric material …”
Section: Nanocellulose Smart Materialsmentioning
confidence: 99%